Investigating the comparative effectiveness of yoga and relaxation therapy on irritability, muscle tension, and sleep problems in patients with rheumatism - Meysam Mozafari (Chronic Diseases Journal, 2025)
BACKGROUND: Rheumatoid arthritis (RA), a debilitating autoimmune disease, has a significant impact on both the physical and mental well-being of those affected due to its long-lasting nature. The study aimed to investigate the comparative effectiveness of yoga and relaxation therapy in improving the control of irritability, increased muscle tension, and sleep problems encountered by individuals with rheumatism.